PENGARUH KOMPETENSI TERHADAP KINERJA DOSEN PADA FAKULTAS EKONOMI, SOSIAL DAN POLITIK UNIVERSITAS MUSAMUS MERAUKE - Samuel Atbar (Universitas Musamus, Merauke, Papua, 2012)
The study focuses on the efforts to reveal the influence of lecturers competence on their performance in the faculty. The research variables are elaborated in some dimensions and indicators. The Competency variables are elaborated into three dimensions : knowledge, skills and self-concept. Meanwhile, the lecturers performance variables are directed to the Three fold university service principles The research is an analytical quantitative study seeking data on respondents by means of questionnaire distributed in a survey. The quantitative data obtained are analyzed with coefficients correlation and determination aimimg at describring the influence of lecturers’ competence on their performance.The study indicates that statistically speaking there is an influence of competence variables (X) on their performance (Y) as much as 0.518 with a contribution of 26.8%. in mean time, the influence of other factors or variable which are not studies under this research on variable (Y) is 73.2%. This implies that an increase or decrease in the lecturers performance is always in line with the increase or decrease of the competence variables so is the opposite. This also means that the decrease in the performance is due to the decrease in competence and the higher the competence, the better the performance of the lecturers.